Rapidly progressive glomerulopathy in a patient with hepatitis C virus not diagnosed. Case Report. - Oscar G. Galindo-Contreras; Alfredo Lom-García; Jimena Sánchez-Zumaya; Nicolás Sánchez-Rodríguez; Clara C. Sánchez-Rodríguez (Annals of Hepatology, 2024)
Introduction and Objectives: Hepatitis C virus (HCV) related-Kidney disease, mostly due to the formation of immune complexes and cryoglobulins with cryoglobulinemic vasculitis (CryoVas), and a direct cytopathic effect. We present a case of HCV-nephritic syndrome associated with focal segmental glomerulosclerosis without CryoVas that reported anecdotally in the literature. Materials and Patients: 63-year-old female with 15 years of stable essential hypertension. She suddenly presented lower extremity edema, headache, phosphenes, hypertensive uncontrol, hematuria, proteinuria and decreased glomerular filtration. She received steroids with partial response, for which phenolic acid was started after six months without complete response. A renal biopsy with immunofluorescence, serum antinuclear antibodies (SS-A, SS-B, Sm, RNP, Jo1, Scl70, dsDNA, ANCA-c, ANCA-p, anticardiolipin, cryoglobulins) rheumatoid factor, C4 electrophoresis of immunoglobulins and liver function tests carry out. Results: All liver and immunological parameters was normal. The renal biopsy were atypical damage associated with HCV finding focal segmental glomerulosclerosis with areas of extra-capillary proliferative glomerulosclerosis pauci-immune, shown in Figure 1. Hepatitis C serology and viral load were positive, she received glecaprevir/pibrentasvir for 12 weeks with a sustained viral response at week 12. During the 3-year follow-up, the patient is on peritoneal dialysis, with no viral relapse. Conclusions: We should emphasize that the control of focal segmental glomerulosclerosis-associated nephritic syndrome was achieved with direct-acting antivirals (AAD). This type of kidney injury is described as a direct lesion from virus replication to direct injury to podocytes, so the isolated use of other immunosuppressive therapies (steroids/immunosuppressors) can accelerate the renal damage, early identification of HCV involvement is necessary to start appropriate treatment with AAD as soon as possible.